PENGEMBANGAN MODUL PEMBELAJARAN BAHASA INDONESIA UNTUK KETERAMPILAN BERBICARA DI KELAS VII SMP AWALUDDIN KABUPATEN KUBU RAYA - Wati, Wati; Aunurrahman, Aunurrahman; Martono, Martono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe development of learning modules is based on the low learning outcomes of learners and the limited teaching materials available in schools. The purpose of the development research is to produce the learning module development design, to describe the learning of Indonesian language by using learning module, and to know the result of learning speaking skill through the use of learning module. This research is development research with Borg and Gall stage: research and data collection, planning, product draft development, expert validation, revision of expert commentary, trial, revision of trial commentary result, and final product refinement. Data collection techniques with observation, interviews, and documentation. Data collection tools are observation sheet, interview guide, and questionnaire. Data analysis used qualitative and quantitative analysis. The results of the study were: (1) research and information collecting, (2) planning stage, (3) development stage, (4) expert validation stage, (5) trial stage, (6) ) refinement of the final product. Learning Indonesian uses learning modules starting with preparation, introduction, core activities (exploration, elaboration, and confirmation), assessing the work of learners, evaluation, and closing. Learning outcomes of learners after the use of learning modules showed an increase, it is seen from the result of pretest 47.5 while the result of posttest 85.3. The increase can also be seen from the result of t test 2 paired samples showing t statistics > t table (36> 1.708), meaning there is difference of learning result using learning module.Key words: Learning modules, speaking skills, learning outcomes